2011
DOI: 10.1002/stem.551
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β Inhibition Promotes Engraftment of Ex Vivo-Expanded Hematopoietic Stem Cells and Modulates Gene Expression

Abstract: Glycogen synthase kinase-3b (GSK-3b) has been identified as an important regulator of stem cell function acting through activation of the wingless (Wnt) pathway. Here, we report that treatment with an inhibitor of GSK-3b, 6-bromoindirubin 3 0 -oxime (BIO) delayed cell cycle progression by increasing cell cycle time. BIO treatment resulted in the accumulation of late dividing cells enriched with primitive progenitor cells retaining the ability for sustained proliferation. In vivo analysis using a Non-obese diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…52 Consistent with this, FOXO3a, mTOR and GSK3β, downstream targets of the PI3K/Akt pathway, have been shown to be crucial modulators of HSC metabolism and quiescence. 19,[53][54][55] Intriguingly, niche signals such as TGFβ, Wnts or OPN could act on HSC fate by blocking this activation process, which would manifest itself by LRC inhibition. 17,23,24 Our experiments also show that other factors affecting LRC had a direct effect on c-Kit (and Sca-1) distribution in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…52 Consistent with this, FOXO3a, mTOR and GSK3β, downstream targets of the PI3K/Akt pathway, have been shown to be crucial modulators of HSC metabolism and quiescence. 19,[53][54][55] Intriguingly, niche signals such as TGFβ, Wnts or OPN could act on HSC fate by blocking this activation process, which would manifest itself by LRC inhibition. 17,23,24 Our experiments also show that other factors affecting LRC had a direct effect on c-Kit (and Sca-1) distribution in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…34,58), and consequently reduced their numbers in the PB. This is supported by the observation that both treatment with FGF-2 or IGF-1 and direct GSK3β inhibition trigger HSPC proliferation in vitro (6,59,60). Obviously, many signaling molecules are essential for HSPC motility and development, however, the functional linkage between HSC retention (i.e., restriction of motility) and self-renewal could be an important foundation for future studies.…”
Section: Scf Enhances Hspc Migration Via Gsk3βmentioning
confidence: 85%
“…In a steady state, low levels of HSPCs are constantly circulating as part of homeostasis, whereas in stress situations, HSPCs are recruited in high numbers from the bone marrow (BM) into the circulation as part of host defense and repair mechanisms (2). Glycogen synthase kinase-3β (GSK3β) is a well-established negative regulator of the Wnt/β-catenin pathway, implicated in self-renewal and development of human and murine HSCs (3)(4)(5)(6)(7)(8)(9)(10)(11). In addition to proliferation, GSK3β has been shown to be involved in the motility of various cells, including microglia, epidermal stem cells, human mast cells, and breast cancer cells (12)(13)(14)(15)(16), but its effect on the motility of immature hematopoietic cells has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that ex vivo Wnt5a-treated young LT-HSCs decreased HSC repopulation ability [126]. Pretreatment with a GSK-3 inhibitor, which activates the canonical Wnt downstream effector -catenin, promotes engraftment of ex vivo-expanded human HSCs in xenografted mice [127,128].…”
Section: Wnts and Glycogen Synthase Kinase 3 (Gsk-3) Inhibitormentioning
confidence: 95%